Pengaruh Kredibilitas Corporate Social Responsibility Terhadap Penilaian Konsumen - Meyliana -; Hanny - (Jurnal Akuntansi, 2019)
Corporate Social Responsibility (CSR) is no longer an option but an obligation for companies in Indonesia and it become legal in the form of President Republic of Indonesian’s laws and in the form of Minister of Environment Regulation. Prior studies show that companies which perform well in the CSR implementation will have better financial performance. This is due to the HALO effect where a good corporate CSR performance will gain good credibility in the eyes of consumers so that consumers appreciate it through purchasing the company's products. The test result using a simple linear regression test model shows that there is no influence of the company's CSR credibility as measured by the acquisition of the Corporate Performance Ranking Program (PROPER) on consumer valuation as measured by the company's total annual sales. 72 data observations were obtained from 7 companies listed on the Indonesia Stock Exchange from 2002-2016 and participated in PROPER activities. Keywords: CSR Credibility, PROPER, Consumer’s Valuation